The Formal Means of Cohesion in the Works of Lithuanian and Foreign Linguists - Remeikytė, Vida (Kalbotyra, 2002)
The article presents a review of the concepts cohesion and coherence in the works of Lithuanian and foreign linguists. Most of all attention is given to cohesion, the formal means of connecting the sentences. First of all coherence is realised by coupling sentences semantically. However, coherence requires a wider context, the interaction of an addressee and an addresser. Coherence is expressed by formal devices as well. The coherent text is apprehended in the subconsciousness of the addressee and the addresser, and the cohesive text is seen exteriorly and is being realised through the levels of language. Due to such a realisation of cohesion, the means of connecting sentences are mostly classified in accordance with traditional taxonomy. They include lexical and lexico-grammatical means.